2005
DOI: 10.14411/eje.2005.082
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge on genes and genomes of phytophagous beetles (Coleoptera: Chrysomeloidea, Curculionoidea): a review

Abstract: Abstract. Fifteen years after the publication of the first genomic sequence of a phytophagous beetle, we review here the wealth of genetic and genomic information generated so far for the species-rich beetle superfamilies Chrysomeloidea (longhorn, seed and leaf beetles) and Curculionoidea (weevils and bark beetles). In this review we briefly describe the most common methods used to investigate the beetle genomes and also compile the nucleotide sequence information stored in public gene databases until December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…This finding could be explained either by the shorter coalescence time of this nuclear gene ( ef1‐α has much smaller effective size than coxI ) or the lower substitution rate compared to mitochondrial genes. Because ef1‐α is generally used as a standard genetic marker in phylogenetic and population genetic studies on beetles (Gómez‐Zurita & Galián ), this gene usually shows species distinctiveness. The exceptions are when hybridization has occurred or lineage sorting is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained either by the shorter coalescence time of this nuclear gene ( ef1‐α has much smaller effective size than coxI ) or the lower substitution rate compared to mitochondrial genes. Because ef1‐α is generally used as a standard genetic marker in phylogenetic and population genetic studies on beetles (Gómez‐Zurita & Galián ), this gene usually shows species distinctiveness. The exceptions are when hybridization has occurred or lineage sorting is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Diapause plays a fundamental role in life cycle synchronization in many insect species (Tauber and Tauber 1976;Denlinger 2002;Gomez-Zurita and Galian 2005), and incorporating descriptions of species-specific diapause regulation into phenological models can be crucial for predicting the response to driving climate variables (Gray et al 2001;Steinbauer et al 2004;Tobin et al 2008). Our study indicated that diapause may determine how far bi-and trivoltinism in I. typographus will expand in a warmer climate, as day length cues could restrict the length of the late summer swarming period unless adaptation occurs.…”
Section: Second Generation Late Swarmingmentioning
confidence: 99%
“…These are frequent markers used in many phylogenetic studies (Gómez Zurita and Galián 2005; Sequeira et al 2008). In addition, a fragment of the nuclear elongation factor 1-alpha gene was analysed for a representative taxon of each morphological group in order to elucidate deeper nodes or for checking controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…For the molecular analysis of the Madeiran clade, only one specimen per taxon and two mitochondrial genes were chosen: fragments of cytochrome oxidase subunit II and of ribosomal 16S RNA subunit. These are frequent markers used in many phylogenetic studies ( Gómez Zurita and Galián 2005 ; Sequeira et al 2008 ). In addition, a fragment of the nuclear elongation factor 1-alpha gene was analysed for a representative taxon of each morphological group in order to elucidate deeper nodes or for checking controversial results.…”
Section: Introductionmentioning
confidence: 99%